Experimental and numerical study on the influence of flow passages in centrifugal fan using computational fluid dynamics - Patel Babubhai, Viral Kumar; Chaudhari, Abhimanyu; Sharma, Ashwani; Diwakar, Vikas (Institute of Physics, 2023)
In this work, three actual impeller geometries of identical size, with backward, radial, and forward flow passages in the same volute casing, are experimentally analysed and numerically simulated to understand the flow physics characteristics and the performance mapping under different flowrate conditions. A grid independence test is carried out for the whole computational domain to capture complex flow behaviour inside blades. The three-dimensional numerical analysis is performed under steady flow conditions, and for a rotational domain, a moving reference frame approach (frozen rotor method) is used. The results obtained from experimental and simulated cases for backward, radial, and forward curved centrifugal fans with varying mass flowrates shows that static pressure and total pressure are increased with an increase in rotation speed and the static pressure gradient is higher in forward curved blades than in backward and radial bladed centrifugal fans. A blade’s low and high-pressure regions along the suction and pressure sides are visualised by numerical analysis. The degree of recirculation within blade passages, flow reversal and vortex formation in volute and tongue regions is observed to be different in all three types of flow passages, which clearly describes its influence on the performance characteristics of centrifugal fans.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: centrifugal fans; computational fluid dynamics; impeller blade; mass flow rate; Impellers; Numerical methods; Vortex flow; Computational fluid dynamics